Question:সরল কর:
ক.`(x - y)/(xy) + (y - z)/(yz) + (z - x)/(zx)`
খ.`(x - y)/((x + y) (y + z)) + (y - z)/((y + z) (z + x)) + (z - x)/((z + x) (x + y))`
গ. ` y/((x - y) (y - z)) + x/((z - x) (x - y)) + z/((y - z) (z - x))`
ঘ.`1/(x + 3y) + 1/(x - 3y) - (2x)/(x^2 - 9y^2)`
ঙ.` 1/(x - y) - 2/(2x + y) + 1/(x + y) - 2/(2x - y)`
চ. `1/(x - 2) - (x - 2)/(x^2 + 2x + 4) + (6x)/(x^3 + 8)`
Answer ক. `(x - y)/(xy) + (y - z)/(yz) + (z - x)/(zx)`
`= (z(x - y) + x(y - z) + y(z - x))/(xyz)`
`= (zx - yz + xy - zx + yz - xy)/(xyz)`
`= 0/(xyz) = 0`
উত্তর: 0
খ.`(x - y)/((x + y) (y + z)) + (y - z)/((y + z) (z + x)) + (z - x)/((z + x) (x + y))`
`= ((x - y)(z + x) + (y - z) (x + y) + (z - x) (y + z))/((x + y)(y + z)(z + x))`
`= (zx + x^2 - yz - xy + xy + y^2 - zx - yz + yz + z^2 - xy - zx)/((x + y)(y + z)(z + x))`
`= (x^2 + y^2 + z^2 - xy - yz - zx)/((x + y)(y + z)(z + x))`
উত্তর: `(x^2 + y^2 + z^2 - xy - yz - zx)/((x + y)(y + z)(z + x))`
গ. ` y/((x - y) (y - z)) + x/((z - x) (x - y)) + z/((y - z) (z - x))`
`= (y(z - x) + x(y - z) + z(x - y))/((x - y)(y - z)(z - x))`
`= (yz - xy + xy - zx + zx - yz)/((x - y)(y - z)(z - x))`
`= 0/((x - y)(y - z)(z - x)) = 0`
উত্তর: 0
ঘ.`1/(x + 3y) + 1/(x - 3y) - (2x)/(x^2 - 9y^2)`
`= (x - 3y + x + 3y)/((x + 3y) (x - 3y)) - (2x)/(x^2 - 9y^2)`
`= (2x)/(x^2 - 9y^2) - (2x)/(x^2 - 9y^2)`
= 0
উত্তর: 0
ঙ. `1/(x - y) - 2/(2x + y) + 1/(x + y) - 2/(2x - y)`
`= (1/(x - y) + 1/(x + y)) - (2/(2x + y) , + 2/(2x - y))`
`= (x + y + x - y)/((x - y) (x + y)) - (2(2x - y) + 2(2x + y))/((2x + y) (2x - y))`
`= (2x)/(x^2 - y^2) - (4x - 2y + 4x + 2y)/((2x)^2 - y^2)`
`= (2x)/(x^2 - y^2) - (8x)/(4x^2 - y^2)`
`= (2x(4x^2 - y^2) - 8x(x^2 - y^2))/((x^2 - y^2) (4x^2 - y^2))`
`= (8x^3 - 2xy^2 - 8x^3 + 8xy^2)/((x^2 - y^2) (4x^2 - y^2))`
`= (6xy)^2/((x^2 - y^2)(4x^2 - y^2))`
`= (6xy^2)/((x^2 - y^2)(4x^2 - y^2))`
চ. `1/(x - 2) - (x - 2)/(x^2 + 2x + 4) + (6x)/(x^3 + 8)`
`= (1(x^2 + 2x + 4) - (x - 2)^2)/((x - 2) (x^2 + 2x + 4) + 6x/(x^3 + 8)`
`= (x^2 + 2x + 4 - (x^2 - 2.x.2 + 2^2))/((x - 2)(x^2 + x. 2 + 2^2)) + (6x)/(x^3 + 8)`
`= (x^2 + 2x + 4 - x^2 + 4x - 4)/(x^3 - 2^3) + (6x)/(x^3 + 8)`
`= (6x)/(x^3 - 8) + (6x)/(x^3 + 8)`
`= (6x(x^3 + 8) + 6x(x^3 - 8))/((x^3 - 8)(x^3 + 8))`
`= (6x^4 + 48x + 6x^4 - 48x)/((x^3)^2 - 8^2) = (12x^4)/(x^6 - 64)`
উত্তর : `(12x^4)/(x^6 - 64)`
ছ. `1/(x - 1) - 1/(x + 1) - 2/(x^2 + 1) + 4/(x^4 + 1)`
`= (x + 1 - x + 1)/((x - 1) (x + 1)) - 2/(x^2 + 1) + 4/(x^4 + 1)`
`= 2/(x^2 - 1) - 2/(x^2 + 1) + 4/(x^4 + 1)`
`= (2(x^2 + 1) - 2(x^2 - 1))/((x^2 - 1) (x^2 + 1)) + 4/(x^4 + 1)`
`= (2x^2 + 2 - 2x^2 + 2)/((x^2)^2 - 1^2) + 4/(x^4 + 1)`
`= 4/(x^4 - 1) + 4/(x^4 + 1)`
`= (4(x^4 + 1) + 4(x^4 - 1))/(x^4 - 1) (x^4 + 1)`
`= (4x^4 + 4 + 4x^4 - 4)/((x^4)^2 - 1^2) `
`= (8x^4)/(x^8 - 1)`
উত্তর `: (8x^4)/(x^8 - 1)`
জ. `(x - y)/((y - z) (z - x)) + (y - z)/((z - x) (x - y)) + (z - x)/(x - y)(y - z))`
`= (x - y)/((y - z) (z - x)) + (y - z)/((z - x) (x - y)) + (z - x)/((x - y) (y - z))`
`= ((x - y)^2 + (y - z)^2 + (z - x)^2)/((x - y) (y - z) (z - x))`
`= (x^2 - 2xy + y^2 + y^2 - 2yz + z^2 + z^2 - 2xz + x^2)/((x - y) (y - z) (z - x))`
`= (2x^2 + 2y^2 + 2z^2 - 2xy - 2yz - 2zx)/((x - y) (y - z) (z - x))`
`= (2(x^2 + y^2 + z^2 - xy - yz - zx))/((x - y) (y - z) (z - x))`
উত্তর: `(2(x^2 + y^2 + z^2 - xy - yz - zx))/((x - y) (y - z) (z - x))`